2008
DOI: 10.1137/070692017
|View full text |Cite
|
Sign up to set email alerts
|

Fast Monte Carlo Simulation Methods for Biological Reaction-Diffusion Systems in Solution and on Surfaces

Abstract: Many important physiological processes operate at time and space scales far beyond those accessible to atom-realistic simulations, and yet discrete stochastic rather than continuum methods may best represent finite numbers of molecules interacting in complex cellular spaces. We describe and validate new tools and algorithms developed for a new version of the MCell simulation program (MCell3), which supports generalized Monte Carlo modeling of diffusion and chemical reaction in solution, on surfaces representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
348
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 305 publications
(355 citation statements)
references
References 22 publications
(44 reference statements)
1
348
0
1
Order By: Relevance
“…788) using a custom binary output format to allow for efficient storage and compression of simulation results. The algorithms underlying MCell have been described in detail in the past (Kerr et al 2008;Stiles and Bartol 2001). For each distinct simulation condition (different numbers of Ca 2ϩ sensor sites on vesicles, varying external Ca 2ϩ concentration, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…788) using a custom binary output format to allow for efficient storage and compression of simulation results. The algorithms underlying MCell have been described in detail in the past (Kerr et al 2008;Stiles and Bartol 2001). For each distinct simulation condition (different numbers of Ca 2ϩ sensor sites on vesicles, varying external Ca 2ϩ concentration, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…1A). Using stochastic reaction-diffusion simulation via MCell (Kerr et al 2008;Stiles and Bartol 2001), we were able to show that a model of the frog NMJ with eight synaptotagmin molecules on each synaptic vesicle (corresponding to 40 Ca 2ϩ binding sites) without any ad hoc Ca 2ϩ binding site cooperativity could predict experimentally known properties of single-action potential-triggered vesicle fusion ). In the current study we found that our previous model was not able to predict the experimentally observed facilitation during multiple stimuli at high frequency.…”
mentioning
confidence: 99%
“…In the microscopic model, individual molecules move by Brownian motion and when they are close they can react with each other. The molecules diffuse in the simulation either by taking small time steps in a solution of a Langevin equation [5,32] or by sampling a probability distribution for the new position [29,40,52]. Such microscopic models are much more computationally demanding than a corresponding mesoscopic simulation, at least for reasonable mesh resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…[2,22,28,50] and for microscopic simulation e.g. [4,32,48,52] of cell biochemistry and diffusion. Some of them are compared in [14], but only a few integrate single molecule models with a meso or macro level model [6,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation